2009
DOI: 10.1245/s10434-009-0708-x
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of Atypical Protein Kinase C λ/ι in Gastric Cancer as a Prognostic Factor for Recurrence

Abstract: Our results suggested that aPKClambda/iota overexpression was a strong prognostic factor for gastric adenocarcinoma recurrence. As well as being a new prognostic indicator, aPKClambda/iota is also likely to be a novel therapeutic target for gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(60 citation statements)
references
References 41 publications
2
56
2
Order By: Relevance
“…We propose that the tumor suppressor function of PAR3 stems, at least in part, from its role in restricting the activity of aPKC. This model is consistent with the reported oncogenic activity of aPKC (8,46,47).…”
Section: Discussionsupporting
confidence: 92%
“…We propose that the tumor suppressor function of PAR3 stems, at least in part, from its role in restricting the activity of aPKC. This model is consistent with the reported oncogenic activity of aPKC (8,46,47).…”
Section: Discussionsupporting
confidence: 92%
“…10,11 Importantly, the PKCl/i gene is located at the 3q26.2 genomic region, which is most frequently amplified in human cancer 16,17 , and overexpression of PKCl/i has been implicated in cancer development in multiple tissues including the lung, 18,19 pancreas, 20 stomach, 21 colon, 22 esophagus, 23 liver, 24 bile duct, 25 ovary, 17 prostate 26 and brain. 27 Recently, few studies have been reported higher expression of PKCl/i in ER/PRand HER-positive breast cancer and also in lymph node metastases.…”
mentioning
confidence: 99%
“…Note PKCι overexpression has been observed in numerous human cancers including cancers of the lung (Regala et al, 2005b), pancreas (Scotti et al, 2010), stomach (Takagawa et al, 2010), colon (Murray et al, 2004), esophagus (Yang et al, 2008), liver (Du et al, 2009), bile duct (Li et al, 2008), breast (Kojima et al, 2008), ovary (Weichert et al, 2003;Eder et al, 2005;Zhang et al, 2006), prostate (Ishiguro et al, 2009), and brain (Patel et al, 2008). PKCι is itself an oncogene, which appears to be activated through tumor-specific overexpression.…”
Section: Various Cancersmentioning
confidence: 99%